PENGARUH PENAMBAHAN LIMBAH PLASTIK JENIS THERMOSETTING TERHADAP MUTU BATA RINGAN (HEBEL) - Supriyadi, Supriyadi; Kusdiyono, Kusdiyono; Wahyono, Herry Ludiro; Utomo, Marchus Budi; Nurhadi, Imam (Politeknik Negeri Semarang, 2020)
At this time, plastic is a material that is needed by the wider community and its impact is also extraordinary after the plastic is used in everyday life which can cause serious problems if the management is not done properly. The problem of plastic waste does not only occur in the city of Semarang, but also in other cities, so that the Ministry of Environment and Forestry to impose a program to use paid plastic bags in the short term. But this is only to deal with problems in the short term. In the long run, it will not solve the problem of